ch41-p006 - 6. Let E1 = 63 meV + EF and E2 = 63 meV + EF....

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
6. Let E 1 = 63 meV + E F and E 2 = – 63 meV + E F . Then according to Eq. 41-6, P ee EE k T x F 1 1 1 1 1 1 = + = + () / where xE E k T F =− / 1 . We solve for e x : e P x = = 1 1 1 0 090 1 91 9 1 . . Thus, 21 2 / / 1 11 1 1 0.91, 1 ( 9 1 / 9 ) 1 FF T T x P e −−
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.
Ask a homework question - tutors are online